Expert considerations and consensus for using dogs to detect human SARS-CoV-2-infections - Sebastian Meller; Maryam Sultan Ali Al Khatri; Hamad Khatir Alhammadi; Guadalupe Álvarez; Guillaume Alvergnat; Lêucio Câmara Alves; Chris Callewaert; Charles Caraguel; Paula Carancci; Anne‐Lise Chaber; Marios Charalambous; Loïc Desquilbet; et al. (2022)
OPINION article Front. Med., 08 December 2022Sec. Infectious Diseases: Pathogenesis and Therapy Volume 9 - 2022 | https://doi.org/10.3389/fmed.2022.1015620